Crystal Structure of Electroceramics - Stevin Snellius Pramana (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Electrical, optical, ionic and magnetic properties of ceramics are primarily dictated by their crystal structure. They can be improved by introducing impurities, creating long range order/short range order/disorder, engineering defects and utilising specific crystal anisotropy and orientation. This Special Issue is aimed at manuscripts focusing on the recent development of electroceramics and its relation to the crystallography, including the characterisation aspect. In particular, the topic of interest covers the review paper on principles, difficulties and progress of crystal structure determination and refinement from powder diffraction, and ferroelectricity in binary crystals. Other interesting piezoelectric, electrical conducting, dielectric and ferroelectric ceramics are reported with various crystal structural characterisation and microscopy techniques.